Uji Aktivitas Antibakteri Ekstrak Etanol Kombinasi Daun Kepel (Stelechocarpus Burahol) dan Pegagan (Centella Asiatica) - Suzan Astyamalia; Maulana Tegar Aditya Nugraha; Ferli Eko (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Kepel and pegagan (kola) leaves have been used as traditional- medicine. Combination kepel and pegagan leaves wasn’t known exactly how its antibacterial activity yet. The purpose of this study was to determine the combination ethanol extract of kepel and kola leaves as antibacterial activity. The method of this study is the well diffusion method. The data were analyzed using quantitative descriptive methods to obtain the minimum, maximum, mean and standard deviation values for the data. The analysis used a descriptive method to explain the antibacterial activity of the ethanol extract of kepel and pegagan leaves against Escherichia coli and Staphylococcus epidermidis with the ratio of kepel and pegagan leaves in extracts 10:90, 30:70, 50:50, 70:30 and 90:10. The results showed that Escherichia coli bacteria had the largest inhibitory diameter in a combination of 70 parts of Kepel leaves and 30 parts of pegagan leaves with an inhibitory diameter of 0.800 cm, while for gram-positive bacteria, Staphylococcus epidermidis, the optimal inhibitory diameter was 0.950 cm in a combination of 40 parts kepel leaves and 60 parts of pegagan leaves. The combination of kepel and pegagan leaves is in providing bacterial inhibition. Escherichia coli bacteria are bacteria that are commonly found in the digestive tract and Staphylococcus epidermidis which generally causes acne.